Ethioipia: Ending hunger and undernutrition: challenges and opportunities - Compact2025 (International Food Policy Research Institute, 2017)
This scoping report was prepared to inform the roundtable discussion by providing an overview of the food security and nutrition challenges and opportunities in Ethiopia. It reviews the current food security and nutrition policy landscape across key sectors and actors in Ethiopia and identifies critical knowledge, policy, and implementation gaps. Additionally, the scoping report presents a SWOT analysis (strengths, weaknesses, opportunities, and threats) that crystallizes the main elements that drive or hamper food security and nutrition in the country. To determine what is holding back progress, the report identifies several key research and action gaps, including generating research on context-specific, agriculturenutrition pathways, synthesizing shareable lessons on success stories in food security and nutrition, and effectively communicating those findings can help to influence decision makers and inform practitioners.